Implementation of Shariah Management Audit to Enhance Economic Efficiency and Financial Health in Pharmacies - Rustan, Rustan; Syamsuddin, Syamsuddin; Idrawahyuni, Idrawahyuni; Nurjanna, Nurjanna; Asmasary, Andi Arwinny; Kusumaningrum, Sheila; Adiningrat, Andi Arifwangsa (International Journal of Economics Development Research (IJEDR), 2024)
Challenges and obstacles faced by Pharmacies such as inventory management, human resource management, and operational cost efficiency are often obstacles in achieving these goals. This study aims to analyze the implementation of sharia management audits in operational efficiency in pharmacies, improve financial health and propose strategic recommendations to identify possible obstacles, future development. This study uses a descriptive research type with a qualitative data analysis method. Data collection techniques are carried out by observation, literature review, and interviews with Pharmacy informants. The results of this study indicate that sharia management audits improve operational efficiency and financial health of pharmacies through waste identification, stock management, transparency of financial reports, and revenue optimization. Strategic recommendations include staff training, sharia-based guidelines, digital technology, and policy support.